Nusyuz dalam Rumah Tangga Perspektif Fiqih Munakahat - Naufal Akbar; Aniq Saeful Rosyad; Adit Munandar; Linda Amelia; Hikmatullah Hikmatullah (STIKes Ibnu Sina Ajibarang, 2026)
Within the framework of Islamic family law (fiqh munakahat), the issue of nusyuz plays a significant role, as it is closely related to maintaining harmony and stability in the marital relationship. Generally, nusyuz is often defined as a form of a wife’s disobedience toward her husband. However, Islamic jurisprudence acknowledges that nusyuz can also be committed by a husband if he fails to fulfill the rights, responsibilities, and obligations he owes to his wife, in accordance with the principles of Sharia. This study aims to provide a comprehensive analysis of the concept of nusyuz in the context of family life, from the perspective of fiqh munakahat. The discussion covers the meaning and characteristics of nusyuz, its legal basis in Islamic sources, the factors contributing to its emergence, its various manifestations in married life, its implications for family relationships, and existing methods for addressing this issue. This study employs a literature review method supported by a descriptive qualitative approach, drawing on relevant literature from classical and contemporary Islamic legal sources. The results indicate that resolving issues of nusyuz should be approached through a gradual and constructive process, including counseling, dialogue, mediation, consultation, and reconciliation. These steps aim to restore mutual understanding and strengthen family unity. Therefore, raising awareness of each spouse’s rights and obligations is crucial to preventing nusyuz and creating a household filled with peace, love, mutual respect, and intimacy.